Comportamiento agronómico y valor nutricional del pasto tanzania (panicum máximum cv.) con abonos orgánicos en diferentes estados de madurez en el campo Experimental La Playita UTC – La Mana - Erazo Molina, Marlon Vicente (2014)
The research entitled "Agronomic behavior and nutritional value of Tanzania pasture (panicum maximum cv.) with organic fertilizers (vermicompost and slaughterhouse waste) in different states of maturity (30, 45, 60 and 75 days) in the experimental field La Playita UTC - La Maná, the objectives to be pursued were to determine the agronomic performance of Tanzania grow with organic fertilizers. To establish the nutritional value of Tanzania grow in different stages of maturity....